Effect of weld parameters on mechanical properties of the friction stir welding AA6063-T5. - Tra, Tran Hung (Asean Engineering Journal)
Effect of tool rotation speed and welding speed on the mechanical properties of the FSW joint of AA6063-T5 was investigated. The influences of the ratio of rotation speed and weld speed on the weld thermal cycle, hardness distribution, and tensile strength of the FSW joint were clarified. The experimental results showed the lower the ratio of rotation speed and weld speed, the lower weld heat input, the narrower the softened zone and the higher tensile strength were. In all cases, the tensile fracture located outside the stirred zone, in the retreating side or advancing side, where the hardness was lowest. It was also found that the residual stress in and around the welded zone was quite low, in range of ten percent of base metal yield stress.